2010
DOI: 10.1016/j.biopha.2010.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical pharmacokinetic analysis of NOV-002, a glutathione disulfide mimetic

Abstract: SummaryNOV-002 is a glutathione disulfide (GSSG) mimetic that is in Phase III clinical trials for the treatment of advanced non-small cell lung cancer and other oncology indications. GSSG is reduced by glutathione reductase (GR) to form glutathione (GSH), thereby maintaining redox homeostasis. The purpose of the study was to report the pharmacokinetic properties of NOV-002 and evaluate the effect that NOV-002 elicits in redox homeostasis. The pharmacokinetic analysis and tissue distribution of NOV-002 and GSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The cone voltages were 23 V, 35 V, and 25 V, and the collision energy 13 V, 22 V, and 12 V, respectively. The redox potential (E h ) of thiol/disulfide levels in the nucleus accumbens was calculated from the GSSG and GSH concentrations using the Nernst equation, E h ¼ 7.4: À264 + 30log (GSSG)/(GSH) 2 (Jones et al, 2000;Uys et al, 2010). The values are expressed in mV ± SEM.…”
Section: Redox Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The cone voltages were 23 V, 35 V, and 25 V, and the collision energy 13 V, 22 V, and 12 V, respectively. The redox potential (E h ) of thiol/disulfide levels in the nucleus accumbens was calculated from the GSSG and GSH concentrations using the Nernst equation, E h ¼ 7.4: À264 + 30log (GSSG)/(GSH) 2 (Jones et al, 2000;Uys et al, 2010). The values are expressed in mV ± SEM.…”
Section: Redox Potentialmentioning
confidence: 99%
“…Given that GSH is the most abundant non-protein cellular thiol and redox buffer (Lopez-Mirabal and Winther, 2008), the redox potential can be calculated using GSH and GSSG concentrations through the Nernst equation (Jones et al, 2000;Schafer and Buettner, 2001;Uys et al, 2010). The E h of thiol/disulfide levels in the nucleus accumbens was calculated from the GSSG and GSH concentrations (see Supplementary Table S1 for raw values).…”
Section: Acute Cocaine Increases Redox Potential (E H ) In Accumbensmentioning
confidence: 99%
“…Besides being used as a single herb, it is also a common constituent of a variety of ayurvedic preparations used in the treatment of chronic malaria, diabetes, hepatic toxicity, common cold and loss of appetite (Cáceres et al, 1999;Chopra et al, 1982;Elango et al, 2011;Kapil et al, 1993;Misra et al, 1992;Rahman et al, 1999;Raina et al, 2013;Roxas & Jurenka, 2007;Zhang & Tan, 2000). Pharmacokinetic studies constitute an important phase in the development of new medicine and also to determine the disposition process (absorption, distribution, metabolism and elimination) for selection of the most appropriate route of administration and dose regimen (Liu et al, 2010;Uys et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the involvement of GST P in cellular signaling was shown with the detection of p38 MAPK, JNK and ERK activation with dose dependent phosphorylation of Akt, JAK2, and STAT5. Clinical studies with NOV-002 were shown the improved tolerance to chemotherapy with increase in survival rate when administered in combination with standard chemotherapeutics in advanced non-small cell lung cancer patients (Townsend et al, 2002;Townsend et al, 2008;Uys et al, 2010). Besides the advancements of cancers in relation to the oxidative stress induced GST activation, recently it was reported that normal keratinocytes may represent a vitiligo-like cytokine pattern after exposure to 4-hydroxy-2-nonenal (HNE), another ROS source.…”
Section: Interaction Of Gst With Proteins In Signal Transduction Pathmentioning
confidence: 99%